A methodological proposal to analyze the labor market of the cultural sector in Santa Catarina (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article proposes a critical methodology, based on Karl Marx's political economy, to analyze the labor market in the Performing Arts in Santa Catarina. In the face of a timid expansion in the sector (1.6% growth in salaried workers over a decade), the study develops a system of indicators to unravel the capitalist relations of production in the cultural field. The results reveal a contradiction: despite the "creative economy" narrative, the domain of the Performing Arts has a minuscule market (488 formal employment contracts), where precariousness is structural. It is concluded that overcoming this scenario requires an alternative political project and the strengthening of workers' collective organization.
Keywords: labor market; cultural sector; production relations; political economy; Santa Catarina